Assistive Technology in Mathematics Education: Investigating the Effectiveness of Math Manipulatives for Students with Disabilities - Widiana, I Wayan; Jampel, I Nyoman; Antara, I Gede Wahyu Suwela (Universitas Pendidikan Ganesha, 2024)
Mathematics education for students with disabilities often faces various challenges, such as difficulties in understanding abstract concepts and limitations in using adaptive media. This study aims to investigate the utilization of math manipulatives as assistive technology to support more inclusive and interactive mathematics learning. Employing a qualitative approach with an exploratory design, data were collected through focus group discussions (FGDs) and in-depth interviews involving teachers and students as primary respondents. Thematic analysis was used to identify patterns in the application of math manipulatives during the learning process. The findings reveal that math manipulatives, such as number boards, numeric cards, and other visual tools, significantly enhance students' comprehension of mathematical concepts concretely. Furthermore, the use of math manipulatives fosters students' learning motivation and active participation, particularly in group work. Additionally, these tools assist teachers in designing lessons that are more adaptive to students’ needs. The study concludes that math manipulatives as assistive technology holds substantial potential to support mathematics education for students with disabilities, addressing both cognitive and affective aspects. The latest information in this research provides an important contribution to the development of science in the field of inclusive education and educational technology.